Sleep Disruption and Proprioceptive Delirium due to Acetaminophen in a Pediatric Patient - Carla Carnovale; Marco Pozzi; Andrea Angelo Nisic; Elisa Scrofani; Valentina Perrone; Stefania Antoniazzi; Emilio Clementi; Sonia Radice (Hindawi Limited, 2013)
We present the case of a 7-year-old boy, who received acetaminophen for the treatment of hyperpyrexia, due to an infection of the superior airways. 13 mg/kg (260 mg) of acetaminophen was administered orally before bedtime, and together with the expected antipyretic effect, the boy experienced sleep disruption and proprioceptive delirium. The symptoms disappeared within one hour. In the following six months, acetaminophen was administered again twice, and the reaction reappeared with similar features. Potential alternative explanations were excluded, and analysis with the Naranjo algorithm indicated a "probable" relationship between acetaminophen and this adverse reaction. We discuss the potential mechanisms involved, comprising imbalances in prostaglandin levels, alterations of dopamine, and cannabinoid and serotonin signalings.